Understanding the Gender Role in E-waste Management: A Textual Analysis Using Hashtag on Instagram - Siswantini Siswantini; Lila Nathania (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
Taking gender issues into consideration when implementing a program or project is often seen as a burden. Understanding gender roles can help decision-makers and policymakers develop better regulations and increase the value of the project or program. However, understanding the role of gender in the e-waste issue could be challenging. This research explores e-waste management through a gender perspective on social media using the hashtag (#) because it is often used as an identification tool in creating various micro-communities. This study focuses on understanding how females and males behave differently when communicating about e-waste on social media. The research questions are: (1) what is the profile and characteristics of #ewaste enthusiasts on Instagram, (2) what user-driven activities are associated with #ewaste being promoted on Instagram, and (3) what the predominant shared values and beliefs within are #ewaste.Â Using a generated list of results when the search query â€œe-wasteâ€ was used, this study found 125 accounts on Instagram that participated in communicating e-waste handling. Data analysis is used to perform a textual analysis of profile biographies and thematic analysis of both visual and textual data to understand gender behaviour in e-waste. The result showed that female participation is easier to understand than male posts through their intention to share information and knowledge using a small story. The male frequently uses a short caption needs further interpretation to understand their post's meaning. Using hashtags helps researchers profile the characteristics of participants in e-waste handling campaigns and how they create a community in social media. This study implies the genderlect theory in the digital era. The difference between the use of language in creating meaning for e-waste handling between men and women. The study concludes that there is a difference in using language as a symbol of communication between men and women in expressing their interest in e-waste management.